2015
DOI: 10.1007/s10900-015-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Healthcare Resources and Colorectal Cancer Outcomes Among Non-Hispanic White and Non-Hispanic Black Adults

Abstract: This study aims to examine if access to healthcare, measured through the availability of medical resources at the neighborhood level, influences colorectal cancer (CRC) stage, treatment and survival using the Surveillance Epidemiology and Ends Result (SEER) dataset (November 2012), linked with the 2004 Area Resource File. A cross-sectional study was conducted to determine the association between availability of healthcare resources and CRC outcomes among non-Hispanic Black (n = 9162) and non-Hispanic White pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Impoverishment may impact health through access to personal health care providers, quality of care, healthcare literacy and availability of effective medical treatments. 18 We found that counties in Sepsis Cluster or Sepsis Belt regions had larger numbers of medical physicians per 100 000 persons, but lower education and income. Our study delineates that persons living in regions with otherwise higher 'access to care' are still at greater odds for sepsis.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Impoverishment may impact health through access to personal health care providers, quality of care, healthcare literacy and availability of effective medical treatments. 18 We found that counties in Sepsis Cluster or Sepsis Belt regions had larger numbers of medical physicians per 100 000 persons, but lower education and income. Our study delineates that persons living in regions with otherwise higher 'access to care' are still at greater odds for sepsis.…”
Section: Discussionmentioning
confidence: 60%
“…In the USA, socio-economic status remains an important determinant of health and mortality. 7,41,42 Whereas geographic and socio-economic differences in diseases such as cancer and cardiovascular disease have been extensively researched, 11,18,27,28,[43][44][45] very few studies have attempted to uncover the community characteristics that predict sepsis risk. We found that community poverty was a weak mediator of the association between region and odds of sepsis, and similarly other studies have indicated that neighbourhood poverty and income are associated with bloodstream and bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 , 18 ] Prior studies have shown that the availability of healthcare resources has significant influence on health outcomes, including breast and colorectal cancer survival. [ 19 21 ] The influence of healthcare availability on health outcomes also appears to vary by race; a higher number of medical personnel and health facilities in US counties was observed not to be significantly associated with reduced late stage presentation and longer survival for Black colorectal cancer patients, but was associated with improved outcomes for White colorectal cancer patients. [ 19 , 21 ] Since Black women are more likely to present with late stage of disease and have higher mortality, despite lower ovarian cancer incidence compared with Whites, [ 22 25 ] examining if and how availability of healthcare resources influences ovarian cancer stage and mortality among Blacks and Whites may improve understanding of the causes of persistent racial disparities, while highlighting potential areas for targeted intervention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to EA, AA have greater age-adjusted CRC incidence per 100,000 individuals (44 AA versus 38 EA) and greater age-adjusted CRC mortality per 100,000 individuals (19 AA versus 14 EA) 1 . These disparities might not be fully explained by differences in screening rates or access to care 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%